Exploring the role of the CapG gene in hypoxia adaptation in Tibetan pigs - Yan, Feifei; Wang, Yu; Wei, Mingbang; Zhang, Jian; Ye, Yourong; Duan, Mengqi; Chamba, Yangzom; Shang, Peng (Frontiers in Genetics, 2024)
The CapG gene, which is an actin-binding protein, is prevalent in eukaryotic cells and is abundantly present in various pathways associated with plateau hypoxia adaptation. Tibetan pigs, which have inhabited high altitudes for extended periods, provide an excellent research population for investigating plateau hypoxia adaptation. This study focused on Tibetan pigs and Yorkshire pigs residing in Nyingchi, Tibet. The blood physiological data of Tibetan pigs were found to be significantly higher than those of Yorkshire pigs, including RBC, HGB, HCT, MCH, and MCHC.The SNP analysis of the CapG gene identified six sites with mutations only present in Tibetan pigs.Notably, the transcription factors at sites C-489T, C-274T, and A-212G were found to be altered, and these sites are known to be associated with hypoxia adaptation and blood oxygen transportation. The mRNA expression of the CapG gene exhibited highly significant differences in several tissues, with the target proteins predominantly higher in the Yorkshire pig compared to the Tibetan pig. Specifically, a notable difference was observed in the lung tissues. Immunohistochemistry analysis revealed high expression levels of CapG proteins in the lung tissues of both Tibetan and Yorkshire pigs, primarily localized in the cytoplasm and cell membrane. In conclusion, the CapG gene plays a significant role in regulating hypoxia adaptation in Tibetan pigs. This study provides a theoretical basis for the conservation and utilization of Tibetan pig resources, the breeding of highland breeds, epidemic prevention and control, and holds great importance for the development of the highland livestock economy.